Correlation between Work Load and Work Period with Blood Pressure among Workers of PT. X - Widajati, Noeroel; Rizkiawati, Nur Laili (Folia Medica Indonesiana, 2019)
Industry that uses technology nowadays, beside having positive impacts, also having negative impacts such as adverse effects on workers and work environment. Every person who works will have workload and responsibility on their work. This will affect health of the workers, including their blood pressure. The purpose of this study was to study the relationship between work load and work period with blood pressure among workers in ship construction company, PT. X. This study was an observational descriptive study, using cross sectional design. Total population involved 41 individuals, taken from the respondents who met the inclusion criteria. Data collection included pulse and blood pressure measurements. Data analysis used in this study was Pearson and Spearman correlation tests. The result showed that there was a level of correlation between blood pressure and age (0.478), blood pressure and work period (0.432), blood pressure and work load (0.448). The conclusions of this study was that blood pressure related to age, nutritional status, work period, work load and noise intensity. PT X needs to pay attention to the health of the workers, such as blood pressure examination, and provide socialization on nutritious foods that are appropriate to the work performed.